Colistin-Resistant mcr-1-Positive Escherichia coli ST131-H22 Carrying blaCTX–M–15 and qnrB19 in Agricultural Soil - Lopes, Ralf; Furlan, João Pedro Rueda; dos Santos, Lucas David Rodrigues; Gallo, Inara Fernanda Lage; Stehling, Eliana Guedes (Frontiers in Microbiology, 2021)
The pandemic Escherichia coli sequence type 131 (ST131) carrying plasmid-mediated colistin resistance mcr genes has emerged worldwide causing extraintestinal infections, with lineages belonging to three major clades (A, B, and C). Clade B is the most prevalent in animals, contaminating associated meat products, and can be transmitted zoonotically. However, the blaCTX-M-15 gene has only been associated with C2 subclade so far. In this study, we performed a genomic investigation of an E. coli (strain S802) isolated from a kale crop in Brazil, which exhibited a multidrug-resistant profile to clinically significant antimicrobials (i.e., polymyxin, broad-spectrum cephalosporins, aminoglycosides, and fluoroquinolones). Whole-genome sequencing analysis revealed that the S802 strain belonged to serotype O25:H4, ST131/CC131, phylogenetic group B2, and virotype D5. Furthermore, S802 carried the clade B-associated fimH22 allele, genes encoding resistance to clinically important antimicrobials, metals, and biocides, and was phylogenetically related to human, avian, and swine ST131-H22 strains. Additionally, IncHI2-IncQ1, IncF [F2:A-:B1], and ColE1-like plasmids were identified harboring mcr-1.1, blaCTX-M-15, and qnrB19, respectively. The emergence of the E. coli ST131-H22 sublineage carrying mcr-1.1, blaCTX-M-15, and qnrB19 in agricultural soil represents a threat to food and environmental safety. Therefore, a One Health approach to genomic surveillance studies is required to effectively detect and limit the spread of antimicrobial-resistant bacteria and their resistance genes.